(3CNHGQ GdCMHGQ HCNHGQ GdBHGQs - (3eMeO Hf CMeO jhQ Hf eMeO Hf CMeO, , GdOjeGfjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd eMeO Hf CMeO jhQ Hf eMeO Hf CMeO Hf eMeO GdYGbd GdOjeGfi dGNdGa Hjf YdeGFfG hCgd GdfSH ef bOeGFfG cSjQ eMeO hGdO UGMH CfSGH Cgd GdUMQGA hTjNI eMeO GdSjOGdi Cf Hfi MSGf CNGge YQH s
(3BNQgG (B:s
(3agPG BNQ eG ef Gddg Hg JYGdi Ydi ef gfg GdCNHGQ hCSeGA GdBHGQ hCSCdg hgh NjQ eSFhd Efg Ydi Pdc bOjQ hHGdCLGHI LOjQ hUdi Gddg Ydi SjOfG eMeO hYdi Bdg UdGI dG fgGjI dgG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eYfhfI HGdMHQ GdCMeQ heRjfI HGdMHQ GdCUaQ s
(3hYdi HYV ghGeTgG JUhjHGJ hTQhM agi ebQhAg s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JQeje s
Keywords: (3GdJGQjNs